The Effect of Empowerment, Training, Compensation through Organizational Commitment on the Performance of the Financial Management of the North Sulawesi Provincial Government - Zainudin Hilimi; Dewi Susita; Paulus Kindangen (Program Studi S3 Ilmu Manajemen, 2020)
This study aims to analyze and determine the effect of empowerment, training, compensation through organizational commitment to the financial management performance of the North Sulawesi Provincial Government. The methodology used in this research is a quantitative approach with a descriptive survey method. Research respondents numbered 267 financial management employees.The results of this study indicate that 1) Empowerment has a direct and positive effect on the performance of financial management employees. 2) Training has a direct and positive effect on the performance of financial management employees. 3) Compensation has a direct and positive effect on the performance of financial management employees. 4) Organizational commitment has a direct and positive effect on the performance of financial management employees. 5) Empowerment of employees has a direct and positive effect on organizational commitment of financial management employees. 6) Employee training has a direct and positive effect on organizational commitment of financial management employees. 7) Compensation has a direct and positive effect on organizational commitment of financial management employees. 8) Empowerment of employees has an indirect and positive effect on employee performance through organizational commitment. 9) Employee Training has an indirect and positive effect on employee performance through organizational commitment. 10) Employee compensation has an indirect and positive effect on employee performance through organizational commitment.